ISSUES OF WESTERN FEMINISM AND ISLAMIC PARADIGM IN #UNINSTALLFEMINISM DIGITAL CAMPAIGN - Eisha Jamila Qomariyah (Leksema: Jurnal Bahasa dan Sastra, 2019)
Feminism has established a debatable topic on the current perceptive related to the social movement for defending women's rights. The aims of this research are to describe Instagram caption and image My body is not mine... and other discourse on social perspective, cultural, Western feminism, and Islamic paradigm. Initiated in early March 2019, the digital campaign carried out the crucial jargon #Uninstallfeminism. The method of the research is three-dimensional CDA (critical discourse analysis) based on Fairclough’s theory focusing on feminism issues that are shown on Instagram account @Indonesiatanpafeminisme and @thisisgender. The analytical data construct from the linguistic features of text implementation, discursive practice, and social practice analysis. The result shows on the linguistic feature of text implementation used much diction to describe the dominant-negative sentences that prevent the Western feminism concept. Antifeminism activists are considered as a movement that is guided by the Islamic paradigm and contrary to Western feminism. However, the notion of discourse is not closely related to Al-Quran and Sunnah. It is a different perspective to understand Western feminism that concern with gender equality based on specific situations. The situation develops on historical, perspective, and ideology. This study of feminism field can be inferred that the digital campaign of #Uninstallfeminism gives a significant impact clarifying on a different perspective based on the text from Western feminism that Indonesian women should be back to the religious rules of Islamic feminism.